Infant mortality - gynaecological and unemployment aspects in Opole Province, Poland - Tukiendorf, Andrzej; Łasocha, Michał; Krasowski, Grzegorz; Orska, Ewa; Porębska, Aleksandra (Central European Journal of Public Health, 2007)
In the study the results of the relation between infant (neonatal + post-neonatal) mortality and the gynaecological and unemployment factors are presented. The fi ndings are based on Bayesian modelling and indicate the possible infl uence of the unemployment situation on mortality, whereas no correlation was found as regards access to the availability of gynaecological health care. The main conclusion is that elevated unemployment which could be referred to a poor socioeconomic situation (amongst other factors) may force pregnant women to pay more attention to improving their life conditions, than to suffi cient medical controlling.
Keywords: Gynecology; Unemployment; Poland; nezaměstnanost; Infant Mortality; gynekologie; Pregnancy Complications; sociální podmínky; Humans; kojenecká mortalita; komplikace těhotenství; lékaři; interpretace statistických dat; Social Conditions; Polsko; Physicians; Data Interpretation, Statistical; lidé